Adeusinho, adeusinho, cousas de religião! (Polifonia, 1997)
ABSTRACT: The present article has the central objective to carry out a comparative study of profane and religious aspects between A Relíquia by Eça de Queiroz and O Evangelho Segundo Jesus Cristo by José Saramago.